Analisis Perjanjian Dalam Transaksi Jual Beli Online Melalui Siaran Langsung di Facebook di Kota Kupang - Marchela Sarianti Tungga; Yossie M. Y. Jacob; Husni Kusuma Dinata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Transactions are legal acts using computers, computer networks, and/or other electronic media. One of the online shopping trends in Indonesia now is shopping using a live broadcast system via the social media Facebook. The system is where the seller displays the goods being sold and states the condition, the type of material, and the price determined by the seller. And if there are interested buyers, there will be a sale and purchase agreement between them. The formulation of the problem in this research is (1) How to implement agreements in online buying and selling transactions via live broadcasts on Facebook. (2) What are the obstacles to implementing the agreement in protecting the rights and obligations of buyers and sellers in online buying and selling transactions via live broadcasts on Facebook?This research is empirical juridical research, with data obtained by interviewing 16 respondents and supported by primary and secondary data, quantitative analysis, and description. The results of this research show that: (1) Implementation of responsibilities for the parties in the sale and purchase agreement at Vmshop-Kupang. Where the implementation of responsibilities has been well regulated in the mutual agreement in the agreement made, but the implementation is still less effective and things are still found that are detrimental to online buyers. (2) The inhibiting factor in implementing the sale and purchase agreement on the Vmshop-Kupang Facebook account is the lack of awareness on both sides regarding the importance of the agreement as a value that protects both parties, namely online buyers and online sellers if a dispute occurs in the future and other factors, namely The time to make a letter of agreement takes a very long time and is complicated so that both parties carry out the agreement with a system of trust without thinking about what will happen in the future.Online buyers must pay proper attention to the procedures for carrying out online buying and selling transactions and the rules that exist in buying and selling transactions as well as the importance of written agreements.